Epitaxial Growth of Flower-Like MoS2 on One-Dimensional Nickel Titanate Nanofibers: A “Sweet Spot” for Efficient Photoreduction of Carbon Dioxide - Khan, Haritham; Kang, Suhee; Charles, Hazina; Lee, Caroline Sunyong (Frontiers in Chemistry, 2022)
Herein, a full spectrum-induced hybrid structure consisting of one-dimensional nickel titanate (NiTiO3) nanofibers (NFs) decorated by petal-like molybdenum disulfide (MoS2) particles was designed through a facile hydrothermal method. The key parameters for tailoring the morphology and chemical, surface, and interfacial properties of the heterostructure were identified for efficient and selective conversion of CO2 into valuable chemicals. Introducing MoS2 layers onto NiTiO3 NFs provided superior CO2 conversion with significantly higher yields. The optimized hybrid structure produced CO and CH4 yields of 130 and 55 μmol g–1 h–1, respectively, which are 3.8- and 3.6-times higher than those from pristine NiTiO3 nanofibers (34 and 15 μmol g–1 h–1, respectively) and 3.6- and 5.5-times higher than those from pristine MoS2 (37 and 10 μmol g–1 h–1, respectively). This improved performance was attributed to efficient absorption of a wider spectrum of light and efficient transfer of electrons across the heterojunction. Effective charge separation and reduced charge carrier recombination were confirmed by photoluminescence and impedance measurements. The performance may also be partly due to enhanced hydrophobicity of the hierarchical surfaces due to MoS2 growth. This strategy contributes to the rational design of perovskite-based photocatalysts for CO2 reduction.